Penerapan Pembelajaran Kooperatif Tipe Make A Match terhadap Hasil Belajar Ips Siswa Kelas IV SD - Rizka Ayu Aslama; Zico Fakhrur Rozi; Elya Rosalina (Journal of Elementary School (JOES), 2022)
This study aims to determine the completeness of social studies learning outcomes after applying the Make A Match type of cooperative learning model in social studies subjects for fourth grade students of SD Negeri 1 Jambu Rejo. The type of research used is Experiment. The research population was all fourth graders of SD Negeri 1 Jambu Rejo, totaling 22 students. Sample selection was done by saturated sampling technique. The sample taken by all fourth graders of SD Negeri 1 Jambu Rejo totaled 22 students and was taught using the Make A Match type of cooperative learning model. The research method used is a quasi-experimental. The data collection technique used a test in the form of essay questions. The data obtained were analyzed using the z-test. Based on the results of the study obtained an average value of 78.33. The results of the z-test analysis obtained > which is 9.92 > 1.64, which indicates that is rejected and is accepted. Thus, it can be concluded that the social studies learning outcomes of fourth graders of SD Negeri 1 Jambu Rejo after using the Make A Match Cooperative Learning Model are significantly complete. Keywords: Application of the Make A Match Cooperative Learning Model, Social Studies Learning Outcomes